2021
DOI: 10.3389/fmicb.2021.686287
|View full text |Cite
|
Sign up to set email alerts
|

Raman Microspectroscopy Goes Viral: Infection Dynamics in the Cosmopolitan Microalga, Emiliania huxleyi

Abstract: Emiliania huxleyi is a cosmopolitan member of the marine phytoplankton. This species’ capacities for carbon sequestration and sulfur mobilization make it a key player in oceanic biogeochemical cycles that influence climate on a planetary scale. Seasonal E. huxleyi blooms are abruptly terminated by viral epidemics caused by a clade of large DNA viruses collectively known as coccolithoviruses (EhVs). EhVs thereby mediate a significant part of material and energy fluxes associated with E. huxleyi population dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…4B ). Similar changes in the nuclear structure were reported previously for infections by NCVs that replicate in cell nuclei ( 55 , 56 ).…”
Section: Resultssupporting
confidence: 87%
“…4B ). Similar changes in the nuclear structure were reported previously for infections by NCVs that replicate in cell nuclei ( 55 , 56 ).…”
Section: Resultssupporting
confidence: 87%
“…However, a higher affinity for phosphate has been described during the night, likely due to higher requirements for cell division (Geider and La Roche 2002). Nutrients acquired up to this stage through the infection are naturally incorporated into EhV biosynthesis as has been recently demonstrated in isotopic labeling experiments with carbon and N (Pasulka et al 2018;Yakubovskaya et al 2021). The reliance of EhV on external phosphate has not been thus far assessed, but likely follows analogous trends.…”
Section: Particulate Organic Matter and Stoichiometry Dynamicsmentioning
confidence: 99%
“…. Nutrients acquired up to this stage through the infection are naturally incorporated into EhV biosynthesis as has been recently demonstrated in isotopic labeling experiments with carbon and N(53,54). The reliance of EhV on external phosphate has not been thus far assessed, but likely follows analogous trends facilitated by the activity of a viral phosphate permease gene encoded by some EhV strains(55,56).…”
mentioning
confidence: 96%
“…SIP-Raman has also been applied to food web studies, tracing movement of carbon from prey to predator ( Li et al, 2013 ). Taking SIP-Raman a step further, Yakubovskaya et al (2021) demonstrated that individual viruses inherited the 13 C-isotopic signatures of their labeled host, Emiliania huxleyi . Similarly, a viral-BONCAT method was used in concert with nanoSIP to track N and C transfer from host to virus during lysis ( Pasulka et al, 2018 ).…”
Section: Investigating Microbial Composition and Activity Using Confo...mentioning
confidence: 99%